2014
DOI: 10.1007/s10616-014-9829-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of urokinase plasminogen activator system by poly(ADP-ribose)polymerase-1 inhibition

Abstract: The urokinase plasminogen activator (uPA) system is a complex regulator of extracellular proteolysis which is involved in various physiological and pathological processes. The major components of this system are the serine protease uPA, two inhibitors PAI-1 and PAI-2, and the receptor uPAR. It has been previously shown by several groups that the uPA system has an important role in cancer progression and therefore its possible prognostic and therapeutic value has been evaluated. The aim of this study is to tack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Our previous experiments showed that A1235 cells had the ability to increase the activity of urokinase plasminogen activator (uPA) when treated with certain drugs [23,24]. We hypothesized that these cells possibly began the process of epithelial-mesenchymal transition, with changes in the uPA activity as a sign of reprogramming.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous experiments showed that A1235 cells had the ability to increase the activity of urokinase plasminogen activator (uPA) when treated with certain drugs [23,24]. We hypothesized that these cells possibly began the process of epithelial-mesenchymal transition, with changes in the uPA activity as a sign of reprogramming.…”
Section: Resultsmentioning
confidence: 99%